2000
DOI: 10.1161/01.str.31.7.1694
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline Worsens Infarct Volume After Transient Focal Ischemia in Rats

Abstract: Background and Purpose-Hypertonic saline (HS) has been advocated as a hyperosmolar agent for the treatment of cerebral edema, especially after traumatic brain injury. We tested the hypothesis that continuous intravenous HS administered during reperfusion from transient focal cerebral ischemia attenuates infarct volume. Methods-Halothane-anesthetized male Wistar rats were subjected to 2 hours of middle cerebral artery occlusion (MCAO) by the intraluminal occlusion technique. At the onset of reperfusion, rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 43 publications
1
42
3
Order By: Relevance
“…In our previous study, the temporal profile of ischemiaevoked increases in brain water content (Toung et al, 2002) suggested a major vasogenic etiology, rather than cytotoxic edema secondary to postischemic energy failure. We have previously shown that institution of a hyperosmolar state with continuous infusion of HS when started at the onset of reperfusion in our rat model of transient focal ischemia worsened infarct volume (Bhardwaj et al, 2000). The explanation for the observed worsening of infarct volume is not readily evident at present, but the mechanism of this detrimental effect was not due to maldistribution of regional CBF.…”
Section: Cerebral Edema After Ischemic Strokementioning
confidence: 72%
“…In our previous study, the temporal profile of ischemiaevoked increases in brain water content (Toung et al, 2002) suggested a major vasogenic etiology, rather than cytotoxic edema secondary to postischemic energy failure. We have previously shown that institution of a hyperosmolar state with continuous infusion of HS when started at the onset of reperfusion in our rat model of transient focal ischemia worsened infarct volume (Bhardwaj et al, 2000). The explanation for the observed worsening of infarct volume is not readily evident at present, but the mechanism of this detrimental effect was not due to maldistribution of regional CBF.…”
Section: Cerebral Edema After Ischemic Strokementioning
confidence: 72%
“…Some experimental data on focal ischemia demonstrate the adverse effects of mannitol on the brain (19). Most of reports on the effects of mannitol have been based on in vivo experiments, in which the effects of mannitol are evaluated by histological examinations based on fixed and stained brain preparations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand mannitol has been reported to worsen the infarct volume after transient focal ischemia in rat cortex, caudoputamen complex, and hemisphere in rats (19). It was also reported that mannitol did not have any effect on energy metabolism in forebrain ischemia (20).…”
Section: Introductionmentioning
confidence: 96%
“…Like mannitol, it may also cause rebound ICH, but the evidences are also less convincing. [65][66] Many studies have compared mannitol with HTS with most in favour of HTS. HTS seems to have a greater and longer lasting reduction of ICP than mannitol, 67 is even effective in decreasing ICP refractory to mannitol 68 and also has less failure rates.…”
Section: Hyperosmolar Therapymentioning
confidence: 99%